NILAI HEROISME DALAM ANIME ONE PIECE “ARC WANO” DARI LAYAR KE REALITAS BUDAYA - Mukhlas, Moch; Sanubarianto, Salimulloh Tegar (ISTIQRA: Jurnal Hasil Penelitian, 2024)
Eiichiro Oda’s anime “One Piece” is known not only for its epic adventure story but also for its deep heroic values. Through the journey of Monkey D. Luffy and his friends in search of the legendary treasure “One Piece," this anime depicts the idea of ​​heroism as a dedication to fighting injustice. This study aims to analyze and identify the values ​​of heroism manifested in the main characters of the anime, especially in the Wano Arc. This study uses a qualitative method with a content analysis approach. Data were obtained through data collection techniques based on literature reviews by analyzing texts in One Piece, especially volumes 900-1084, which tell the Wano arc. Data analysis techniques were carried out by examining elements of heroism such as courage, responsibility, solidarity, and never giving up shown by the main characters. The results of the study show that the Wano Arc consistently displays heroic values ​​through the struggle against oppression and injustice, which provides inspiration and relevance for the younger generation in facing social challenges in the contemporary era. This research recommendation encourages educators and content creators to use the heroic values ​​of One Piece as a medium for character learning for the younger generation, as well as encourage further research related to the application of these values ​​in various socio-cultural contexts